2002
DOI: 10.1139/f01-202
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization dynamics in rainbow trout (Oncorhynchus mykiss): effect of male age, social experience, and sperm concentration and motility on in vitro fertilization

Abstract: We examine aspects of the fertilization dynamics of rainbow trout (Oncorhynchus mykiss) that may play a role in determining reproductive success of males of different age and status competing for spawning. There were no differences in the gonadosomatic indices and relative yields of milt of adult (3-year) and precocious (1-year) male rainbow trout collected from a wild population. The concentration of sperm in the milt of precocious males was higher than that of adult males. The duration of sperm motility was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 27 publications
4
74
3
Order By: Relevance
“…2. The results fall in line with Liley et al (2002) and Tekin et al (2003) who reported that spermatocrit value decreases with increasing age.…”
Section: Discussionsupporting
confidence: 92%
“…2. The results fall in line with Liley et al (2002) and Tekin et al (2003) who reported that spermatocrit value decreases with increasing age.…”
Section: Discussionsupporting
confidence: 92%
“…Similar tendencies were found by Liley et al (2002) for rainbow trout, where adult males exposed to nesting females had a greater proportion of active sperm compared to unexposed males kept in all-male groups, although the difference was not significant. Differences in fertilization rates could however not be detected in that study (Liley et al 2002).…”
Section: Discussionsupporting
confidence: 76%
“…The swimming activity during the initial 5 -10 s after activation can be crucial to the outcome of sperm competition. In tests with rainbow trout, over 80% of 50-100 eggs were fertilized within the first 10s, using the same sperm concentration as in our study (Liley et al 2002). It is possible that the >30s motility measured in this study does not accurately reflect potentially important differences in motility occurring during the first 10s.…”
Section: Discussionmentioning
confidence: 77%
“…All of the models assume that males obtain more fertilization success by releasing more sperm, this being done at a cost to investment in other fitness-enhancing functions such as growth, finding additional males, investment in female function, mate defence, territoriality or releasing more sperm in other spawnings. As applied to fish, sperm-competition trials with paternity analysis have been conducted in several salmonid species (Gage et al 1995, Gile & Ferguson 1995, Liley et al 2002 and recently also in cyprinids (Kortet et al 2004, Reichard et al 2004a, 2004b or other species such as bluegill sunfish (Lepomis macrochirus; Burness et al 2004). In rainbow trout (Oncorhynchus mykiss) male potency, defined as the ability of males to sire progeny when their sperm is pooled with that of other males, was not affected by the female gametes used, and decreased significantly when sperm concentrations were equalized (Gile & Ferguson 1995).…”
Section: Introductionmentioning
confidence: 99%